2014
DOI: 10.1603/en14079
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Competitive Displacement of Native Ant Fauna by Invading <I>Myrmica rubra</I> (Hymenoptera: Formicidae) Populations

Abstract: Exotic ants have become invasive in many regions around the world, with variable ecological impacts. Postinvasion, native ant communities are often found to be depauperate, though the causes of this apparent lack of coexistence are rarely well known. Myrmica rubra (L.), a Palearctic Myrmecine ant, is currently expanding its range as an invasive in North America. This aggressive ant forms dense, patchy local infestations and appears to aggressively displace native ant fauna. We measured behavioral interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…in natural settings (along with laboratory and mesocosm settings, similar to this study; Meadley-Dunphy et al, 2016;Prior et al, 2014Prior et al, , 2015. Garnas et al (2014) found that M. rubra recruited to baits faster than native ant species in its invasive range in Maine. Gammans, Drummond, and Groden (2018) found that M. rubra moved more seeds than the native ant species, M. detrinodis and Crematogaster cerasi, also in forests in Maine.…”
Section: Discussionsupporting
confidence: 80%
“…in natural settings (along with laboratory and mesocosm settings, similar to this study; Meadley-Dunphy et al, 2016;Prior et al, 2014Prior et al, , 2015. Garnas et al (2014) found that M. rubra recruited to baits faster than native ant species in its invasive range in Maine. Gammans, Drummond, and Groden (2018) found that M. rubra moved more seeds than the native ant species, M. detrinodis and Crematogaster cerasi, also in forests in Maine.…”
Section: Discussionsupporting
confidence: 80%
“…Urbanised areas may serve as habitat and corridors for dry-adapted and heat tolerant species such as ants 39,40 , and such habitats select for opportunistic, highly competitive ant species 41,42 . Lasius niger and Myrmica rubra live in colonies of several thousand individuals, showing aggressiveness and displacement against competitors 43,44 , both species are omnivores with varied diet which consists of honeydew, other invertebrates, pollen, seeds and human waste 45 and are good candidates for benefitting from urban habitats 46 . Indirect interactions between ants and other natural enemies can be complex 47 .…”
Section: Discussionmentioning
confidence: 99%
“…All infestations of this polygynous species are in locations where they will be difficult to eradicate. Myrmica rubra is highly competitive and aggressive in defending resources from other ant species in northeastern United States, and high-density populations can completely displace native ant populations (Garnas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%